Coward a criminal edition - Brubaker, Ed.; Phillips, Sean. (New York Marvel, 2007)
Meet Leo, who can plan the perfect heist...but only if he can be convinced the job is safe enough. See, Leo is not a shoot-first think later guy; Leo is a professional. But to some criminals, even professionals, the right payout is worth almost any risk. So when an old friend and a crooked cop approach with a plan to seize millions of dollars in contraband from an evidence transport van, Leo must make tough choices, knowing there?s nothing you can trust less in this world that a cop on the take" -- P. [4] of cover.
"Contains material originally published in magazine form as Criminal #1-5" -- Cover verso.
Keywords: Thieves -- Comic books, strips, etc. -- Fiction; Suspense comic books, strips, etc; Graphic novels